PP.19.26: NATRIURETIC PEPTIDE CLEARANCE RECEPTOR IS INDUCED BY INSULIN AND IS ASSOCIATED WITH CLINICAL METABOLIC PARAMETERS. (June 2015) - Sarzani, R.; Bordicchia, M.; Ceresiani, M.; Pocognoli, A.; Pavani, M.; Spannella, F.; Muzzonigro, G.; Polito, M.; Wabitsch, M.; Cannone, V.; Jr, J.C. Burnett; Dessì-Fulgheri, P.
Abstract : Objective: The natriuretic peptide (NP) system is involved in systemic cardio-renal regulation but also in lipolysis and "fat burning" in adipocytes. The signaling receptor NPRA and the clearance receptor NPRC mediate the response to NP that is largely dependent on the ratio between of the expression of the two receptors. Adipocytes are distributed through the body and, by NPRC binding, affect also NP levels and their cardio-renal effects. NPRC is selectively downregulated by starving or very low calorie diet favoring lipolysis whereas insulin, stimulated by food ingestion, is an antilipolytic hormone with sodium retaining effects. Design and method: Therefore we examined the insulin- mediated regulation of NP receptors in differentiated human adipocytes and tested the association between NP receptors expression in visceral adipose tissue, insulin, insulin resistance index and metabolic profiles in patients undergoing renal surgery. Differentiated adipocytes (SGBS cell line and primary visceral human adipocytes) were treated with insulin with or without wortmannin, a specific PI3K inhibitor of the main insulin signaling pathway that also inhibits lipolysis in adipocytes. Results: We observed a potent insulin -mediated and glucose dependent up-regulation of NPRC through the PI3-K pathway in differentiated adipocytes. No effect was observed on NPRA. In the patients, an expression ratio in favor of NPRC in adipose tissue was associated with higher fasting insulinemia, higher HOMA index and higher total, LDL and non-HDL cholesterol. Conclusions: In conclusion, insulin and glucose dependent NPRC induction in adipocytes, especially in the contest of insulin resistance and increased insulin levels, might be a key factor linking hyperinsulinemia, metabolic syndrome and higher blood pressure.